THE CONVERGENCE OF ARGUMENT-DRIVEN INQUIRY AND STEM/STEAM: PATTERNS, TRENDS, AND RESEARCH GAPS - Roshifa, Za'ima Nabila; Parno, Parno; Munfaridah, Nuril (EduFisika: Jurnal Pendidikan Fisika, 2025)
The integration of Argument-Driven Inquiry (ADI) with STEM and STEAM approaches has gained attention in recent years due to their shared emphasis on inquiry, collaboration, and real-world problem solving. However, a comprehensive synthesis of how this integration has been researched is still lacking. This scoping review aims to map the trends, patterns, and gaps in studies focusing on ADI-STEM/STEAM integration in secondary science education. Following the PRISMA 2020 guidelines for scoping reviews, literature was collected from Scopus and Google Scholar using a range of relevant keywords. Thirteen eligible articles published up to April 2025 were analyzed based on publication type, country, research method, subject, and focus. Findings show that research on ADI-STEM/STEAM integration began in 2020 and is primarily concentrated in Indonesia. Most studies used mixed methods and focused on physics education, with key variables including conceptual understanding and argumentation skills. However, creative thinking, reflective thinking, scientific literacy, and self-efficacy remain underexplored—particularly within the ADI–STEAM context. Only one study was categorized as a development study, indicating opportunities for designing specialized instructional tools or media to support integration. This study is the first to systematically map ADI-STEM/STEAM research trends using a scoping review approach. Its novelty lies in providing a structured and visualized synthesis of an emerging field. The results offer important insights for educators and researchers seeking to expand innovative, interdisciplinary, and inquiry-based practices in science education.